Vascular remodeling and media calcification increases arterial stiffness in chronic kidney disease. (May 2014) - Gauthier-Bastien, Alexandra; Ung, Roth-Visal; Larivière, Richard; Mac-Way, Fabrice; Lebel, Marcel; Agharazii, Mohsen
Abstract Background: Cardiovascular disease is the most common cause of death in patients with chronic kidney disease (CKD). Arterial stiffness and calcification are non-traditional risk factors of cardiovascular disease in CKD. In CKD rats, we investigated the involvement of smooth muscle cells differentiation to osteoblast-like cells and blood vessel wall remodeling, associated with media calcification, in arterial stiffness. Method: CKD with vascular calcification was induced by subtotal nephrectomy followed by treatment with a high calcium and phosphate diet, and vitamin D supplementation (Ca/P/VitD). At week 3–6, hemodynamic parameters and pulse wave velocity (PWV) were assessed. Vascular media calcification and remodeling were determined by histological von Kossa staining and confocal immunofluorescence analysis of osteocalcin, elastin, α-smooth muscle actin (α-SMA) and collagen-1. Results: Treatment of CKD rats with Ca/P/VitD, but not normal animals, induced a significant increase in pulse pressure and PWV (p < 0.05) and marked calcification in the media. In calcification areas, de novo expression of osteocalcin was observed, whereas α-SMA immunofluorescence levels were reduced (p < 0.01). The immunofluorescence levels of elastin were also reduced, which was related to disruption of elastic lamella. In contrast, collagen-1 immunofluorescence levels in areas of calcification were increased (p < 0.01). Changes in both α-SMA and elastin inversely correlated with the PWV. Conclusion: This study indicate that smooth muscle cells differentiation to osteoblast-like cells and the associated media remodeling, which includes disruption of elastic lamellas and deposition of collagen are, at least in part, associated with the increased arterial stiffness observed in CKD rats with vascular calcification.